Visión ambiental: Retos y oportunidades para las empresas de servicios públicos - Zuleta, Claudia Martínez (Tecnogestión: Una mirada al ambiente, 2011)
This paper studies the principal environmental challenges and issuesthat the public utilities of electricity, water and sewage, sanitation,natural gas and the Information and Communication Technologies –ICT- will have to face in the short-term (2010-2014). In the secondpart the most relevant environmental issues are presented, as wellas the actions that are being developed to face them and that will benecessary in the short, medium and long-term. The last part presentsthe challenges of the new government and the need of a long-termvision to create a balance between authentic competitiveness and sustainabledevelopment.